2020
DOI: 10.3390/ijerph17165799
|View full text |Cite
|
Sign up to set email alerts
|

Association between Personal Social Capital and Loneliness among Widowed Older People

Abstract: To explore the association between the personal social capital and loneliness among the widowed older adults in China. Data from 1497 widowed older adults were extracted from China’s Health-Related Quality of Life Survey for Older Adults 2018. The Chinese version of the Personal Social Capital Scale (PSCS-16) was used to evaluate the participants’ status of bonding and bridging social capital (BOC and BRC). Loneliness was assessed by the short-form UCLA Loneliness Scale (ULS-8). Multiple linear regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 59 publications
2
28
1
Order By: Relevance
“…A previous study has evidenced that determining the risk factors of loneliness is of importance to prevent loneliness [12]. Some factors such as females [11], advanced age [13], low level of educational attainment, and socioeconomic status [14], residing in rural areas [15] have been identified as having a greater odds of developing loneliness in later life. Additional factors including physical inactivity, living alone, retirement, and loss of companions or friends were associated with a higher risk of loneliness among older individuals [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has evidenced that determining the risk factors of loneliness is of importance to prevent loneliness [12]. Some factors such as females [11], advanced age [13], low level of educational attainment, and socioeconomic status [14], residing in rural areas [15] have been identified as having a greater odds of developing loneliness in later life. Additional factors including physical inactivity, living alone, retirement, and loss of companions or friends were associated with a higher risk of loneliness among older individuals [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Subjects were asked to respond to each item with answers ranging from 1 = "never", 2 = "seldom", 3 = "usually", 4 = "often", and 5 = "more often", where each number indicated the associated score accordingly. The score ranges for each dimension were obtained by summarizing answers to each item as follows; social participation (4-20), social support (4-20), social connection (3-15), trust (3-15), cohesion , reciprocity (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). A higher score denoted a better social capital.…”
Section: Measurement Of Social Capitalmentioning
confidence: 99%
“…In a study conducted in 14 European countries, social capital, including regular social participation was linked to a decreased experience of loneliness and a reduction in the impact of loneliness in low-income families [14]. A prior study found that social capital (bonding social capital and bridging social capital) was associated with loneliness among rural widowed older people in China [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations